Transient conformation changes in chromatin during excision repair of ultraviolet damage to DNA. - Bodell, W J (1981)
DNA labeled for 15 minutes during UV induced repair synthesis is two-fold more sensitive to micrococcal nuclease than the bulk nuclear DNA. As the length of the labeling period increases from 15 minutes to 4 hours the nuclease sensitivity of repair labeled DNA approaches that of bulk chromatin. Pulse-chase experiments indicate that the nuclease sensitivity of the repaired DNA labeled during a brief pulse decreases with a half-life of about 15 minutes. In contrast to previous interpretations, we consider these results to mean that immediately after synthesis, chromatin labeled during repair has a conformation which renders it more susceptible to nuclease digestion than the bulk chromatin. With time these repaired regions are assembled into a nucleosome structure with normal nuclease sensitivity.